Clone Characteristics Of Sil 04, 6535, Ps 881, And Bululawang Polycross - Yulaikah, Sri; Djumali, Djumali; Herwati, Anik; Abdurrakhman, Abdurrakhman; Supriyono, Supriyono; Mulyani, Sri; Sohri, M. (International Journal of Science, Technology & Management, 2023)
Indonesia’s sugar productivity is low and requires improvement. Producing new superior sugar varieties may increase sugar productivity. In 2019, a polycross between female SIL 04 and male 6535, PS 881, and Bululawang made 11 potential clones. Therefore, it is necessary to determine each clone's characteristics. This research aimed to determine superior clones that generate higher crystal production than the female parents. The research location was the Agricultural Technology Research and Assessment Installation (Instalasi Penelitian dan Pengkajian Teknologi Pertanian - IP2TP) Karangploso from December 2020 until November 2021. The clones and female parents (SIL 04) were arranged in a Randomized Block Design using 2 replications. The research result showed that 9 clones (MLG 19/P6/1, MLG 19/P6/4, MLG 19/P6/5, MLG 19/P6/6, MLG 19/P6/8, MLG 19/P6/9, MLG 19/P6/11, MLG 19/P6/13 and MLG 19/P6/16) produced more crystals (7.07-12.95 t/ha) than the female parents (5.82 t/ha). To sum up, increasing sugarcane productivity improves crystal yields.